The behaviour of boron compounds in treated rattan when dehydrated at high temperatures - Ashaari, Zaidon; O. C., Musgrave; J. A., Petty (Universiti Putra Malaysia Press, 1998)
The behaviour of boron compounds per se and boron compounds in treated stem of rotan manau (Calamus manan A1iq.) dried at elevated temperatures was studied. When borax and boric acid are mixed, sodium 1:5 borate is formed. After drying at 100±30, 50±10, or <O°C, the measured and the calculated (in parentheses) percentage weight losses from the mixtures were 40.34 (40.10), 39.31 (36.39) and 29.43% (30.11 %), respectively. The experimentally measured values were used to estimate the amount of solute retained in the rattan samples which had been treated with such a boric acid-borax mixture and then dried. The further weight losses of the mixture in treated rattan dried at higher temperatures are presumably attributable to: 1. the volatilization of low molecular weight rattan components; 2. the volatilization of boric acid in water vapour during drying and 3. the mechanical loss of permeating liquid during the early stage of drying. Treatments of rattan or other cellulosic material which involve boric acid in aqueous solution should avoid high temperature drying in order to ensure optimum retention of boric acid equivalent (BAE).